Heart failure in paediatric Crohn’s disease patient – extraintestinal manifestation, concomitant disease or iatrogenic effect? - Snehil Swaraj; Erzsébet Szakos; László Ablonczy; Csaba Vilmányi; Ádám Goschler; Áron Cseh (Cardiologia Hungarica)
Inflammatory bowel disease encompasses Crohn’s disease and ulcerative colitis, gastrointestinal conditions associated with increased risk of cardiovascular issues compared to those without that. These cardiovascular problems may include pericarditis, myocarditis, thromboembolism, arrhythmias, endocarditis, heart failure, Takayasu arteritis, valvulopathies, and atrioventricular block. However, limited literature exists on this topic in paediatric patients. The primary treatment for Crohn’s disease, the anti-tumor necrosis factor agent infliximab, has been linked to rare but serious cardiovascular complications. Here, we present a case study of a 7-year-old boy with Crohn’s disease whose cardiopulmonary function deteriorated after receiving infliximab therapy.